Langue croisée – Walter Benjamins Erinnerungsarbeit zwischen Hören und Sehen, Paris und Berlin - Daniel Kazmaier (Recherches Germaniques)
Walter Benjamin’s Berlin childhood around 1900 impressively demonstrates his double identity as a Francophone and as a Germanophone author. The edition of all the texts belonging to this memorial project, consisting in several versions, reworkings, compilations, and, last but not least, written in two languages, now provides a solid foundation for research work. With textual-genetic and poetological analyses the article traces Benjamin’s memory work in his Berlin childhood. It is tied to the places of Paris and Berlin, interweaves the sensuality of hearing and seeing, and finally maps this interweaving in the language itself as a langue croisée. Philologically, this article reconstructs Benjamin’s transpositions first by looking on the way he reworked the early Berlin to the late Paris version; then by comparing the pieces Die Mummerehlen and Loggien; and finally his transfer of a section from Die Mummerehlen into the French text Peintures chinoises à la Bibliothèque nationale.